The passage of Maori land into Pakeha ownership: a Maori view - Williams, Betty Whaitiri (Cabbage Tree, 1983)
Keywords: colonisation; history; kōrero nehe; land alienation; land loss; land march; land tenure; land theft; mana whenua; missionaries

He tipua: the life and times of Sir Āpirana Ngata - Walker, Ranginui (Penguin Books, 2002)
Keywords: apirana ngata; biography; history; ngāti porou; politicians; social conditions

Apirana Turupa Ngata (Victoria University Press, 1996)
Keywords: apirana ngata; biography; history; kōrero taumata; ngāti porou; political and social views; rerenga kōrero; te reo maori sources; whakapapa

Panguru and the city: kāinga tahi, kāinga rua : an urban migration history - Williams, Melissa Matutina (Bridget Williams Books, 2015)
Keywords: history; social conditions; social networks; te rarawa; urbanisation

A fire in the belly of Hineāmaru: a collection of narratives about Te Tai Tokerau tūpuna - Webber, Melinda; O'Connor, Te Kapua (Auckland University Press, 2022)
Keywords: history; kōrero nehe; kōrero taumata; northland; rangatira; tūpuna; whakapapa

Tainui and the Treaty of Waitangi = Tainui me te Tiriti. - Toataua, Huti (Kirikiriroa 1990 Community Committee?, 1991)
Keywords: government relations; history; kīngitanga; land tenure; raupatu; tainui; tiriti o waitangi/treaty of waitangi; waikato

Rapaki wahine whakamaumahara: memories of the Rapaki Branch Māori Women's Welfare League - Plumridge, Elizabeth (Canterbury University Press, 2008)
"Documenting the early days of the Rapaki Maori Women's Welfare League, this recollection strives to authenticate the oral histories of the early members that created the opportunity for Maori and Pakeha women to meet and trade skills. As membership of the branch changes, fewer and fewer people can speak with authority on the league's evolution, but this history chronicles the available facts and anecdotes that demonstrate the development of this important union."–BOOK JACKET.
Keywords: history; mana wāhine; māori womens welfare league; social conditions; wāhine māori

Te pooti Maaori: Maaori representation and electoral reform - Farrell, Michael Kevin (Centre for Maaori Studies & Research, University of Waikato, 1992)
Keywords: government; history; mmp electoral system; suffrage

Mana wahine Maori: selected writings on Maori women's art, culture and politics - Te Awekotuku, Ngahuia (New Women's Press, 1991)
Keywords: history; lesbianism; mana wāhine; political activity; wāhine māori

Ngāti Kahu: portrait of a sovereign nation: history, traditions and Tiriti o Waitangi claims / Kia pūmau tonu te mana motuhake o ngā hapū o Ngāti Kahu - Mutu, Margaret; Pōpata, Lloyd; Williams, Te Kani; Herbert-Graves, Ānahera; Rēnata, Reremoana; Cooze, JudyAnn; Pineaha, Zarrah; Thomas, Tania; Kingi-Waiaua, Te Ikanui; Te Rūnanga-a-Iwi o Ngāti Kahu; Wackrow Williams and Davies Ltd (Huia Publishers, 2017)
"This book describes the iwi of Ngāti Kahu through the traditions and histories of each of the sixteen hapū, told by kuia and kaumātua and kept alive for future generations. These include histories of poverty, deprivation and marginalisation at the hands of the Crown, and loss of lands of the iwi. The book examines the range of techniques used by the Crown to justify its actions and the way these laid the groundwork for continuing injustices. The remedies needed to redress these injustices and achieve reconciliation of Ngāti Kahu and the Crown are set out. These include constitutional change to achieve the restoration of political, social and economic well-being to Ngāti Kahu, Crown relinquishment of all Ngāti Kahu lands to their rightful owners and payment of sufficient compensation to ensure no further Treaty of Waitangi claims. This history of Ngāti Kahu details the range of Crown actions against Ngāti Kahu to the current day, the effects of these actions on the people of Ngāti Kahu and the concerted and continuing efforts by Ngāti Kahu for remedies and reconciliation with the Crown"–Publisher information.
Keywords: colonisation; constitutional transformation; government relations; hapū; history; kāwanatanga; kōrero nehe; mana motuhake; ngāti kahu; noho-ā-iwi; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; treaty claims; tūpuna

Ko te whenua te utu = Land is the price essays on Maori history, land and politics. - Sorrenson, M. P. K. (Auckland University Press, 2014)
For more than half a century, Keith Sorrenson - one of New Zealand's leading historians and himself of mixed Maori and Pakeha descent - has dived deeper than anyone into the story of two peoples in New Zealand. In this new book, Sorrenson brings together his major writing from the last 56 years into a powerful whole, covering topics from the origins of Maori (and Pakeha ideas about those origins), through land purchases and the King Movement of the nineteenth century, and on to twentieth-century politics and the new history of the Waitangi Tribunal.
Keywords: colonisation; history; kīngitanga; kōrero nehe; land tenure; tiriti o waitangi/treaty of waitangi; waitangi tribunal

Weeping Waters: The Treaty of Waitangi and Constitutional Change - Mulholland, Malcolm; Tawhai, Veronica (Huia Publishers, 2010)
Weeping Waters is a must read for anyone who wants to be informed about the current debate regarding the Treaty of Waitangi and a constitution for Aotearoa New Zealand. The book features essays from eighteen well-known and respected Maori figures including Professor Margaret Mutu, Bishop Muru Walters, Judge Caren Fox and lawyer Moana Jackson. This is the first book in recent years to offer a M?ori opinion on the subject of constitutional change. It shows how M?ori views have been ignored by successive governments and the courts and how M?ori have attempted to address constitutional issues in the past. The book also provides suggestions for a pathway forward if the Treaty of Waitangi is to be fully acknowledged as the foundation for a constitution for Aotearoa New Zealand.
Keywords: constitution; history; māori views

Hīkoi: Forty Years of Māori Protest - Harris, Aroha (Huia Publishers, 2004)
Hikoi is a photographic history of Maori protest - the public face, the rationale, the organisation and the toil behind the scenes. The images and accompanying text tell the story of protests that were turning points: Springbok Tour demonstrations and Raglan, Bastion Point and Waitangi, the Tent Embassy at Parliament in 1972, the Maori Land March 1975 and Hikoi 2004. Hikoi gives a glimpse of some of the hard-earned fruits of those protests: some traditional lands returned to Maori, the Waitangi Tribunal established, te reo Maori made an official language, Maori medium education and Maori media.
Keywords: hikoi; history; protest; rangatiratanga